Sustainable Provisioning Systems: Extending Alderson’s Transvection Analysis to Detect Value Loss, Power Asymmetry and Underperforming Markets - Wooliscroft, Ben; Wilkes, James (Springer Science and Business Media LLC, 2025)
Business research has offered many tools to understand the opportunity for single firms to create or realise value in the provisioning system. The majority of sustainability tools also relate to single firms, or households. Sustainability is a whole of system shift and we require tools to understand the relationship between different members of the provisioning system and the distribution of costs (internal and externalities) and profits through the system. Building on the work of Wroe Alderson, we provide a tool—the extended transvection—to analyse a provisioning system that provides insights into: information flows, value creation/capture/loss, risk, externalities, equity and fairness, and underperforming provisioning systems. Together these insights allow us to see the sustainability of the provisioning system. The extended transvection also allows for considering scenarios regarding adjusted/alternate provisioning systems.
Keywords: 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; 1505 Marketing; 3506 Marketing